Carbon Monoxide Binding by Hemoglobin and Myoglobin under Photodissociating Conditions - Brunori, Maurizio (1972)
Carbon monoxide binding by myoglobin and hemoglobin has been studied under conditions of constant illumination. For hemoglobin, the homotropic heme-heme interaction (cooperativity) and the heterotropic Bohr effect are invariant with light intensity over a 1000-fold change of c(½). The dissociation constant, measured as c(½), increases linearly with light intensity, indicating that photodissociation is a one-quantum process. At sufficiently high illumination the apparent enthalpy of ligand binding becomes positive, although in the absence of light it is known to be negative. This finding indicates that light acts primarily by increasing the “off” constants by an additive factor. The invariance of both cooperativity and Bohr effect raises a perplexing issue. It would appear to demand either that the “off” constants for the various elementary steps are all alike (which is contrary to current ideas) or that the additive factor is in each case proportional to the particular “off” constant to which it is added (a seemingly improbable alternative).